Advertising : from fundamentals to strategies - Rothschild, Michael L. (D.C. Heath, 1987)
This book is about: An introduction to the World of advertising; Situation analysis and marketing research; Objectives and positioning; Message strategies; Media strategies; Nonadvertising strategies; ...